Edukasi B2SA Pada Ibu-Ibu PKK di Kelurahan Desa Jasem - Satria Bagus Hendra P; Ririt Iriani Sri S; Putra Perdana (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2022)
Diverse, nutritious, balanced, and safe food (B2SA) is an aspect that needs to be applied in daily life, specifically applied to the diet of each individual, because each individual has different needs in meeting their nutritional components. Therefore, counseling about B2SA is very important to increase self-awareness of eating patterns that create a healthy lifestyle. In this case, the physical health of each individual in daily life is reflected in a healthy diet. This service method uses pre-test, counseling, and post-test. The pre-test was carried out before being given counseling to test the extent of the mothers' understanding of healthy eating patterns. The counseling material about the B2SA menu was carried out through discussion and question and answer methods using a tool (Microsoft Powerpoint) as a learning medium. Then, the post-test was carried out after the mothers received counseling. The results of this counseling and education showed that PKK mothers experienced an increase in knowledge about B2SA when judged from the answers to the pre-test and post-test that had been done.